Impact of calsporin® (Bacillus subtilis C-3102) supplementation on growth performance and intestinal function in geese - Guangquan Li; Huiying Wang; Xianze Wang; Lei Yang; Guangpei Xu; Daqian He (Poultry Science)
The objective of this study was to preliminarily explore the effects of Calsporin® (Bacillus subtilis C-3102) on the growth performance, intestinal morphology, apparent digestibility, and cecal microbiota of geese. A total of 144 Sanhua geese, aged 35 days, were randomly divided into three groups: a control group, a group receiving a basal diet supplemented with 30 ppm Bacillus subtilis (B. subtilis), and a group receiving a basal diet supplemented with 60 ppm B. subtilis. Each group had six replicates, with eight geese per replicate. The study consisted of a one-week pre-feeding period followed by a four-week experimental period. The results indicated that, compared to the control group, the group supplemented with 60 ppm B. subtilis showed a significant increase in final body weight and the average daily gain (P < 0.05). Both the 30 ppm and 60 ppm B. subtilis groups exhibited significant improvements in the feed/gain (F/G) ratio (P < 0.05). Additionally, supplementation with either 30 ppm or 60 ppm B. subtilis significantly increased the height of the ileum villi (P < 0.05), with a trend towards an increased villus height to crypt depth (VH/CD) ratio (P > 0.05). In terms of digestive enzyme activity, both 30 ppm and 60 ppm B. subtilis supplementation significantly enhanced the activities of ileum cellulase and chymotrypsin (P < 0.05). Furthermore, the apparent digestibility of crude ash, crude protein, and Ca was significantly improved in the 60 ppm B. subtilis group (P < 0.05). Microbial analysis revealed that B. subtilis increased the abundance of potential probiotics bacterial families, such as Turicibacter, and butyrate-producing, including Prevotellaceae Ga6Al. In conclusion, supplementation with 60 ppm B. subtilis can significantly enhance the growth performance, intestinal morphology, and apparent digestibility of geese. Increasing the supplementation level may further optimize these benefits.